PEMBELAJARAN BERBASIS PROYEK TERHADAP KEMAMPUAN PEMAHAMAN KONSEP SISWA PADA MATERI BANGUN DATAR DI SD - Averlin Kristiani Lahagu; Hardi Tambunan; Firman Pangaribuan (Afore : Jurnal Pendidikan Matematika, 2026)
This study aimed to determine the effect of project-based learning on students’ conceptual understanding of plane geometry at Bintang Laut Private Elementary School, Telukdalam. The study employed a quantitative approach using a quasi-experimental method. The research subjects were fifth-grade students divided into an experimental group and a control group. The experimental group was taught using the project-based learning model, while the control group received conventional instruction. The research instrument was a conceptual understanding test on plane geometry administered before and after the treatment (pretest and posttest). The collected data were analyzed using descriptive and inferential statistics to identify differences in students’ conceptual understanding. The results revealed a significant improvement in students’ conceptual understanding in the experimental group after the implementation of project-based learning compared to the control group. Students taught through project-based learning demonstrated better abilities in understanding the properties of plane figures, applying formulas for area and perimeter, and relating mathematical concepts to real-life situations. These findings indicate that project-based learning is effective in enhancing elementary school students’ conceptual understanding of mathematics. Therefore, project-based learning is recommended as an innovative and contextual instructional strategy in elementary mathematics education.